2020
DOI: 10.3390/molecules25030604
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antitumor Effects on Drug-Resistant Breast Cancer of Paclitaxel/Lapatinib Composite Nanocrystals

Abstract: Drug resistance presents serious difficulties for cancer treatment. A combination of paclitaxel (PTX) and lapatinib (LAPA) shows potentials in multiple drug resistant cancers in the clinic, but it is almost impossible to deliver these two drugs to the tumor at the same time with the best proportion by simple co-administration of the respective current formualtions for their different pharmacokinetic profiles. Here composite nanocrystals of PTX and LAPA (cNC) were designed with a ratio of 2:1 (w/w), which was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Similar nanocrystal complex formed by the cocrystallization of two or more drugs have been proven to effectively increase drug efficacy and reduce toxicity compared with a single drug . However, preparation of previously reported nanocrystal complexes usually involves the use of a toxic organic solvent with a time-consuming and complicated process. In this study, homogeneous nanocrystal complexes could be easily obtained by using a self-assembling peptide to control the crystallization process of RVC and DOX, indicating a facile strategy for fabricating composite drug nanocrystals.…”
Section: Resultsmentioning
confidence: 89%
“…Similar nanocrystal complex formed by the cocrystallization of two or more drugs have been proven to effectively increase drug efficacy and reduce toxicity compared with a single drug . However, preparation of previously reported nanocrystal complexes usually involves the use of a toxic organic solvent with a time-consuming and complicated process. In this study, homogeneous nanocrystal complexes could be easily obtained by using a self-assembling peptide to control the crystallization process of RVC and DOX, indicating a facile strategy for fabricating composite drug nanocrystals.…”
Section: Resultsmentioning
confidence: 89%
“…The reason for the decrease in stability might be that the PDA layer could produce adhesiveness and noncovalent interactions such as hydrogen bonding, and π–π stacking, resulting in the possible aggregation and size increase of nanoparticles. 47 For improving the long-term storage stability of 5-FU@ZIF-8@PDA in practical use, they could be stored in dry form. Furthermore, the stability of the nanoparticles during the skin penetration experiment was investigated as well, and the result is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dissolution of nanocrystals results in the release and subsequent dissolution of the probes in water, which enables unrestricted motion of the probe molecules and extinguishes the fluorescence. By hybridizing TPE with paclitaxel nanocrystals, Li’s group demonstrated that intact nanocrystals of paclitaxel could be internalized by HT-29 and KB cells [ 86 ]. The molecular dynamics of the uptake and exocytosis of THPE nanocrystals by KB cells in their own crystalline and molecular forms was further investigated [ 87 ].…”
Section: Prospectsmentioning
confidence: 99%